2020
DOI: 10.1177/0194599820907303
|View full text |Cite
|
Sign up to set email alerts
|

Primary Paraganglioma of the Facial Canal: An Evidence‐Based Approach

Abstract: Objectives To perform an evidence-based review evaluating presenting symptoms, imaging, and management for primary paragangliomas of the facial canal (PPFCs). Data Sources PubMed/MEDLINE, Embase, Cochrane Library, and Web of Science. Review Methods Studies were assessed for quality of evidence and bias with the Cochrane bias tool, GRADE, and MINORS criteria. Demographic data, imaging modalities, management strategies, and status at last follow-up were obtained. Results Sixteen studies met inclusion criteria. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Another unique feature of the MRI is the “dural tail sign.” The dural tail sign is an en plaque linear dural enhancement along the floor of the middle or posterior cranial fossa. 18 Glomus jugulare paraganglioma 19 can be distinguished from it according to the characteristics of the “salt-pepper sign” or “serpentine effusion” on MRI, and enhanced MRI has higher sensitivity. 20 Gadolinium-enhanced MRI is superior to CT scan in distinguishing peripheral extension of intracranial meningioma and primary extracranial meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Another unique feature of the MRI is the “dural tail sign.” The dural tail sign is an en plaque linear dural enhancement along the floor of the middle or posterior cranial fossa. 18 Glomus jugulare paraganglioma 19 can be distinguished from it according to the characteristics of the “salt-pepper sign” or “serpentine effusion” on MRI, and enhanced MRI has higher sensitivity. 20 Gadolinium-enhanced MRI is superior to CT scan in distinguishing peripheral extension of intracranial meningioma and primary extracranial meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation and treatment methods described in the current case are thus exceptional. Yuhan et al 12 2020 recently published a systematic review of primary paraganglioma of the facial canal documents 21 reported cases in the literature found in case reports and case series. In their review the most common presenting symptom was facial nerve dysfunction, the most common CT finding was an expanded descending facial nerve canal, all studies with MRI findings noted enhancement with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent systematic review of primary paraganglioma of the facial canal documents 21 reported cases in the literature found in case reports and case series. 12 In this report, we describe the case of a 66-year old Hispanic female with ''BP'' that presented to the plastic surgery clinic with a complaint of left facial paralysis. After a thorough workup, a lesion involving the facial nerve from the tympanic segment to the stylomastoid foramen was discovered, ultimately the lesion was found to be a facial nerve paraganglioma…”
mentioning
confidence: 99%
See 1 more Smart Citation